A history of Dumalag, Capiz (1595-1945). - Palenzuela, Ma. Andrea F
This is a historical reconstruction of the town of Dumalag, Capiz from 1595 to 1945 especially on the social, political and religious dimensions of the town. It aims to achieve the following objectives: (1) Describe the society of Dumalag upon the coming of the Spaniards; (2) Present the social, political, and religious changes in the town introduced by the Spanish colonizers; (3) Portray the social, political as well as religious changes introduced during the American Period; and (4) Find out if there are changes in social, political, and religious changes in the town during the Japanese occupation., The researcher employed oral history method, which primarily focused on interview schedule. She also referred to the documents prepared by the Augustinian priests like Fray G. de San Agustin, Fray J. Medina, and Fray Manuel Buzeta and Felipe Bravo, which were all translated in English by Fr. Marcelino in his unpublished article , "The Missionaries in Dumalag", is available in Capiz Museum. She also utilized the published or unpublished documents found from the UPV and San Agustin libraries; Municipal Planning and Development Organization in the Municipal Hall of dumalag; and from M. Advincula's (1973) "Maragtas San Dumalag"; and S. Fuerte's, "War-Time Reminiscences of an Eye-Witness". From the documents prepared by the Augustinian priests, the researcher found out that the early natives of Dumalag were strongly animistic. When the Spanish missionaries attempt to introduced roman Catholicism they met with strong resistance as shown by the Ates and babaylanes revolt of 1799. she also found out that the Spaniards had transformed the town into one of the most beautiful in the province of Capiz. during the American colonial rule, the Americans transformed only the social and political dimension of the town since they only stayed in the place in a short period of time. They did not tamper its religious institutions, thus the natives remained faithful to the Catholic faith. During the Japanese Period, the social, political and religious dimensions of the town did not fully changed by the Japanese since the people were mostly in the mountains.